Beban Glikemik Diet Diabetes Melitus, Tingkat Konsumsi Energi, Protein, dan Serat Kaitannya dengan Kadar Glukosa Darah Pasien Diabetes Melitus Tipe 2 - NISRINA, OKTAVIANI SALWA; Sulistyowati, Etik; Luthfiyah, Fifi; Sutjiati, Endang (NUTRITURE JOURNAL; Vol 3 No 2 (2024): Nutriture JournalDO - 10.31290/nj.v3i2.4200, 2024)
Background : Prevalence of DM in Level II Hospital Dr. Soepraoen Malang at 3.1%. A reduction in blood glucose can be achieved with a low glycemic load. Study how consumption of energy, protein and fiber relates to blood glucose levels. Objective : To determine the relationship between the glycemic load of a DM diet, the level of energy, protein and fiber consumption and the blood glucose levels of Type 2 DM patients. Method : This study uses analytical and design observational research survey cross sectional . The sample used was 15 inpatients with a diagnosis or history of Type 2 DM on 24 May-12 June 2023. The sampling technique used accidental sampling . Data analysis uses Spearman rank correlation. Results : Most of the patients were aged 55-64 years, female, not working, had normal nutritional status, had complications in the cardiovascular system, and were given a type of insulin treatment by a doctor, the glycemic load of the patient's DM diet was low, the patient's level of energy consumption was low, the level of consumption of protein is balanced between poor and good, and the patient's fiber consumption level is good . Conclusion: There is no relationship between the glycemic load of the DM diet, the level of energy consumption, and fiber with the blood glucose levels of Type 2 DM patients at the Level II Hospital, dr. Soepraoen Malang. There is a relationship between the level of protein consumption and the blood glucose levels of Type 2 DM patients at Level II Hospital dr. Soepraoen Malang. Keywords: Glycemic Load, DM Diet, Consumption Level, Nutrients